The metabolic regimes of flowing waters. (12th October 2017) - Bernhardt, E. S.; Heffernan, J. B.; Grimm, N. B.; Stanley, E. H.; Harvey, J. W.; Arroita, M.; Appling, A. P.; Cohen, M. J.; McDowell, W. H.; Hall, R. O.; Read, J. S.; Roberts, B. J.; et al.
Abstract: The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.